How the Financial Performance of Coal Mining & Metal, and Mineral Mining Companies in Indonesia's Stock Market From 2017 to 2022 Influenced Their Stock Prices - Zhou, Li (Universitas Muhammadiyah Jakarta, 2024)
This research ascertained the effect of return on asset, debt to equity, company size, and current ratio on stock prices. The study applied descriptive quantitative. The method includes library research that utilizes data from secondary sources. The population in this study are all coal mining, metal, and mineral mining companies registered on the Indonesia Stock Exchange in the 2017-2022 period. Using the purposive sampling method, 26 companies are obtained with a total of 31 data observations. In analysing the data, the research used panel data analysis (fixed effect). Meanwhile data testing was done by using the E-views 10 program. The findings revealed that partial return on assets and company size had an effect on stock prices, whereas debt-to-equity and current ratios had no effect on stock prices. The study found that several factors which are return on asset, debt-to-equity, company size, and current ratio all simultaneously impact stock prices.